(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article discusses the use of pulsed radiofrequency ablation (HDI) of the spinal ganglia for the treatment of postoperative radicular pain syndrome (PCBS). PCBS is a common complication after spinal surgery, often leading to chronic pain and a decrease in the quality of life of patients. HDI is a minimally invasive method that allows you to purposefully affect the nerve ganglia responsible for pain impulses, with minimal damage to the surrounding tissues. The study involved 50 patients with chronic pain that did not respond to conservative treatment. The results showed a significant reduction in pain intensity by 70% on the visual analog scale (VAS) and an improvement in the quality of life in 80% of patients. The procedure turned out to be safe, without serious complications. Thus, HDI demonstrates high efficiency and safety in the treatment of PCBS, offering a promising solution for patients suffering from chronic pain syndrome after spinal surgery.